The mitochondrial protein TIMM44 is required for angiogenesis in vitro and in vivo - Zhou-rui Ma; Hong-Peng Li; Shi-zhong Cai; Sheng-Yang Du; Xia Chen; Jin Yao; Xu Cao; Yun-Fang Zhen; Qian Wang (Cell Death and Disease, 2023)
Abstract The mitochondrial integrity and function in endothelial cells are essential for angiogenesis. TIMM44 (translocase of inner mitochondrial membrane 44) is essential for integrity and function of mitochondria. Here we explored the potential function and the possible mechanisms of TIMM44 in angiogenesis. In HUVECs, human retinal microvascular endothelial cells and hCMEC/D3 brain endothelial cells, silence of TIMM44 by targeted shRNA largely inhibited cell proliferation, migration and in vitro capillary tube formation. TIMM44 silencing disrupted mitochondrial functions in endothelial cells, causing mitochondrial protein input arrest, ATP reduction, ROS production, and mitochondrial depolarization, and leading to apoptosis activation. TIMM44 knockout, by Cas9-sgRNA strategy, also disrupted mitochondrial functions and inhibited endothelial cell proliferation, migration and in vitro capillary tube formation. Moreover, treatment with MB-10 (“MitoBloCK-10”), a TIMM44 blocker, similarly induced mitochondrial dysfunction and suppressed angiogenic activity in endothelial cells. Contrarily, ectopic overexpression of TIMM44 increased ATP contents and augmented endothelial cell proliferation, migration and in vitro capillary tube formation. In adult mouse retinas, endothelial knockdown of TIMM44, by intravitreous injection of endothelial specific TIMM44 shRNA adenovirus, inhibited retinal angiogenesis, causing vascular leakage, acellular capillary growth, and retinal ganglion cells degeneration. Significant oxidative stress was detected in TIMM44-silenced retinal tissues. Moreover, intravitreous injection of MB-10 similarly induced oxidative injury and inhibited retinal angiogenesis in vivo. Together, the mitochondrial protein TIMM44 is important for angiogenesis in vitro and in vivo, representing as a novel and promising therapeutic target of diseases with abnormal angiogenesis.